Transforming the Spirituality of the Faithful Through Participatory Catechesis: A Theological and Empirical Inquiry - Agustinus Manfred Habur (Riviera Publishing, 2025)
This article examines how participatory catechesis can serve as a catalyst for transforming the spirituality of the faithful by integrating theological reflection with empirical insights from a rural Catholic community in Flores, Indonesia. Despite the regularity of parish activities, many communities continue to experience a devotional life marked by routine participation, limited personal reflection, and minimal integration of faith into daily life. Drawing on the framework of Shared Christian Praxis, experiential learning theory, and contemporary theological understandings of Christian spirituality, this study investigates how dialogical, reflective, and experience-based catechesis can deepen spiritual awareness and foster interior transformation. Employing a qualitative descriptive design, data were collected through interviews, participant observation, and document analysis in Stasi Waekekik of Paroki Mok, Flores, Indonesia. The findings reveal that participatory catechesis enhances engagement, encourages critical reflection on lived experiences, strengthens communal identity, and nurtures a spirituality rooted in active discipleship rather than passive observance. The study concludes that participatory catechesis is a vital pastoral approach capable of renewing the spiritual life of the faithful, particularly in rural communities where traditional didactic methods remain dominant. Practical recommendations are offered for catechists, parish leaders, and pastoral agents to cultivate catechetical environments that promote spiritual growth through participatory, contextual, and transformative learning.